Multi-site calibration of SWAT for the spatial distribution of sediment yield, Middle Awash Dam watershed, Ethiopia - Tesema, Tesfu Abebe; Lam, Kuok-Choy; GebreMariam, Bogale; Tefera, Wasu Manawko (Penerbit Universiti Kebangsaan Malaysia, 2021)
Multi-site calibration of sediment yield has a significant effect on evaluating the spatial distribution of sediment yield of watershed and reservoirs sedimentation. Multi-site calibration was conducted at three gauging stations of the Proposed Middle Awash Dam watershed. The sequential Uncertainty fitting (SUFI-2) calibration uncertainty program (SWAT-CUP) has been used to calibrate and validate flow and sediment parameters using monthly flow and sediment rate observed data. P-factor and R-factor measured model calibration and uncertainty where the P-factor recorded 0.56-0.86/0.54-0.77 and R-factor 0.52-0.93/0.68-0.84 values respectively during the calibration and validation period for the three gauging stations. Model result showed the performance model was excellent during the calibration period with the coefficient of determination R2=0.78-0.82, Nash-Sutcliffe Efficiency ENS=0.77-0.79, Observation Standard Deviation Ratio RSR=0.44-0.48 and percent bias PBIAS=-13.3 to +14.3. Following the calibration process, the model estimated mean annual spatial distribution of sediment yield 7.23 ton/ha/yr at the outlet. Sediment yields spatial distribution showed that among the 19 sub-watersheds ranked based on their sediment yield contributions, eight sub-watersheds have a slope greater than 5%, which is relatively steeper and contributed average annual sediment yields of 16 ton/ha/yr. The temporal variability hydrograph showed 70.8 % of yearly sediment yield in the study area during the rainy season. The study results informed to development of watershed management strategies to minimize the sediment problems in the entire watershed.